Prostate Cancer in Primary Care, Port Harcourt, Nigeria - Bock-Oruma, Andrew (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: Prostate cancer (PC) is under-researched in primary care settings in the developing world, and diagnostic modalities available to the primary care physician could limit the making of the diagnosis, thus affecting the prevalence. AIMS: This study aims to determine the prevalence of prostate cancer in patients that presented with LUTS to a family medicine clinic, using the screening tools (DRE and PSA) available in the facility. SETTINGS AND DESIGN: A cross-sectional study of middle-aged and elderly men that presented to the Family Medicine Clinic, University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria, with LUTS. MATERIALS AND METHODS: Consenting and eligible males that presented to the Family Medicine Clinic with LUTS were assessed for prostate cancer using the PSA and digital rectal examination (DRE) between October 2010 and April 2012. Data were entered and analyzed using the statistical package for the social sciences (SPSS) version 16.0. Association between the variables was compared using chi-Square test with statistical significance set at P < 0.05. RESULTS: Two hundred and ninety subjects participated in the study; the mean age of the subjects was 62.50 ± 11.66 years with an age range of 40 to 100 years. The prevalence for DRE-detected abnormal prostate was 13%, suggestive of PC. One hundred and sixty-one (55.5%) of the subjects had their PSA done and results retrieved, with 51.6% of them having PSA values within the normal range of 0-4 ng/ml, and 48.4% had PSA values outside the normal limits. An association of PSA and DRE gave 24.2% prevalence for probable PC and a significant association between elevated PSA and DRE. CONCLUSION: The diagnostic modality in study is inconclusive, but it offers the family physician the opportunity of improving the quality of life of the patient that presented to him with PC by initiating early referral for secondary care.